Research on BIM Collaborative Design in Overseas Large-Scale Hydropower Engineering and Its Applications - FAN Shaopeng; LIU Huibo; XIONG Zebin; ZHOU Song; LYU Changhuo (Renmin Zhujiang)
Caculo-Cabaça Hydropower Station is an international large-scale hydropower project in Angola,which is designed,constructed,and managed according to European and American standards. Its engineering design is based on the digital three-dimensional (3D) collaborative design platform of Dassault CATIA V5 and 3DExperience,and thus a multi-disciplinary BIM collaborative design mechanism is constructed,which includes topographic surveying,geology,various buildings of the main power station (civil engineering,electromechanics,metallic structure,architecture,monitoring),diversion tunnels,and cofferdam.During different stages of the project,practice and efforts have been made regarding the scheme selection and demonstration,parametric and standard fine design and modeling,numerical analysis,engineering drafting,quantity surveying,etc.The main purpose is to solve the problems such as the optimization and development of two-dimensional (2D) engineering drafting functions based on modeling information,as well as the 3D reinforcement for complex-shaped structures. In this way,this research can provide effective support for the efficient and fine design management of the whole life cycle of the project.